CONFLICT BETWEEN FISHERMEN IN MADURA; CAUSES AND SOLUTIONS - Winarwati, Indien; Hasanah, Uswatun (Jurnal Dinamika Hukum, 2016)
Low productivity leads to competition among fishermen to get fish catches are becoming increasingly stringent because the regime of fish resources management is open (open access). These conditions are prone to conflict. This research is normative-qualitative research, design and method are combination of normative research methods and sociological research methods. There were many factors that cause conflicts between fishermen in Madura that erroneous perception about the ownership of the sea, differences in use of fishing tool, and violations of fishing area. The Conflict is resolved between the head of the fishermen's group, which was attended by village officials and community leaders. If that not works, the village officials will involve Pol.Airud, KAMLA, and the Department of Fisheries and Marine Affairs, and the results are set forth in the form of a written agreement.Â Keywords : conflict between fishermen, causes of conflict, resolution of conflict, MaduraÂ